2018
DOI: 10.3233/wor-182685
|View full text |Cite
|
Sign up to set email alerts
|

Posture and discomfort assessment in computer users while using touch screen device as compared with mouse-keyboard and touch pad-keyboard

Abstract: Touch screen caused more deviated postural angles, increased body discomfort and unfavorable postures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is in line with similar studies that found neck pain to be a common symptom among computer users, ranging from 19% to 70% ( 11 13 , 28 , 29 ). Touch screen devices, according to Kargar et al, necessitate more hand and head movements, resulting in arm/neck pain ( 30 ). Another study found that 68% of participants experienced musculoskeletal pain as a result of using touch screens, with neck pain and upper shoulder pain reported at 84.6% and 65.4 %, respectively, due to unnatural sitting positions without adequate back support ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with similar studies that found neck pain to be a common symptom among computer users, ranging from 19% to 70% ( 11 13 , 28 , 29 ). Touch screen devices, according to Kargar et al, necessitate more hand and head movements, resulting in arm/neck pain ( 30 ). Another study found that 68% of participants experienced musculoskeletal pain as a result of using touch screens, with neck pain and upper shoulder pain reported at 84.6% and 65.4 %, respectively, due to unnatural sitting positions without adequate back support ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]23,24 Touch screen devices, according to Kargar et al, necessitate more hand and head movements, resulting in arm/neck pain. 25 Another study found that 68% of participants experienced musculoskeletal pain as a result of using touch screens, with neck pain and upper shoulder pain reported at 84.6% and 65.4 %, respectively, due to unnatural sitting positions without adequate back support. 26 Logaraj et al, who found that 60.7 % of medical students reported neck pain as the most common symptom of DES, reported similar ndings.…”
Section: Discussionmentioning
confidence: 99%
“…Varying response times of the touch display and the keyboard, possibly also differences of input and output delays that may originate in the manner of implementation, including the toolkits being used, may have an impact here. In addition, there are human factors to consider (46), and these may for example be related to differences in posture between using a keyboard or a touch interface when interacting with the app (47), or a user's perception of tactile effects when using the different input methods (46,48). For the test order, with average latency values decreasing with each additional test, it seems sensible to conclude that faster response times may be due to increasing practice.…”
Section: Principal Findingsmentioning
confidence: 99%